PEMBELAJARAN NILAI GOTONG ROYONG DALAM ARISAN PERNIKAHAN MELAYU SAMBAS - M Basri; Achmadi Achmadi (Jurnal Visi Ilmu Pendidikan, 2022)
AbstractThis research was conducted to analyze the tradition of marriage gathering and the learning process of the value of mutual cooperation in marriage gathering in the Sambas Malay custom. This research was conducted with a qualitative approach, while the type of research is phenomenology, located in Sambas Regency, with research informants involving 8 people who are the Sambas Malay tribe. Data collection techniques using in-depth interviews. The data analysis process was carried out with three stages of activities carried out simultaneously, namely reducing data, presenting data, and establishing conclusions. The findings of the study indicate: (1) marriage gathering, which is better known as a union or jimpitan, is a form of mutual cooperation and togetherness in the Sambas Malay community; & (2) the Sambas Malay community often involves their children in marriage arisan, which is intended to teach their children the value of mutual cooperation, about how to ease the burden of the high cost of marriage, which is borne jointly with the same mechanism. can be accounted for. Keywords: values, mutual assistance, marriage gathering. AbstrakPenelitian ini dilakukan untuk menganalisis tradisi arisan pernikahan dan proses pembelajaran nilai gotong-royong dalam arisan pernikahan dalam adat Melayu Sambas. Penelitian ini dilakukan dengan pendekatan kualitatif, adapun jenis penelitiannya adalah fenomenologi, berlokasi di Kabupaten Sambas, dengan informan penelitian yang melibatkan 8 orang masyarakat yang merupakan suku Melayu Sambas. Teknik pengumpulan data menggunakan indepth interview. Proses analisis data dilakukan dengan tiga tahap kegiatan yang dilaksanakan secara bersamaan yakni me-reduksi data, menyaji data, dan menetapkan simpulan. Temuan penelitian menunjukkan: (1) arisan pernikahan yang lebih dikenal dengan persatuan atau jimpitan merupakan wujud gotong-royong dan kebersamaan dalam masyarakat Melayu Sambas; & (2) masyarakat Melayu Sambas seringkali melibatkan anak-anak mereka dalam arisan pernikahan, yang dimaksudkan untuk membelajarkan anak-anak mereka nilai gotong-royong, tentang bagaimana saling meringankan beban biaya pernikahan yang cukup tinggi, yang ditanggung secara bersama-sama dengan mekanisme yang dapat dipertanggungjawabkan. Kata Kunci: nilai, gotong-royong, arisan pernikahan